FOREIGN (TERRORIST) FIGHTERS AND THEIR FAMILIES: CHALLENGES FOR STATE INSTITUTIONS AND THE BORDER MANAGEMENT OF ESTONIA AND THE EU - Belova-Dalton, Oksana (Border Security and Management, 2023)
Foreign terrorist fighters (FTFs) returning with their families to the countries of origin in the EU after the fall of ISIS caliphate in Iraq and Syria, as well as foreign fighters (FFs) returning to the EU after combating in the conflict zones in (Eastern) Ukraine present a significant challenge for public institutions and border management of the EU member states. While there is differing legislation across member states regarding the treatment of foreign fighters in Ukraine, there are largely common views on and framework for prosecution of FTFs, deradicalisation and reintegration of them and their families, which requires a remarkable multi-agency effort as exemplified by member states like Finland and Sweden. Having served their sentences, FTFs and, possibly, also FFs have a clean profile, but there remains a risk that some of them may resume terrorism-related activities. In this article, questionnaire as well as semi-structured interviews were used to establish how Finland, Sweden, and the Baltic States are handling the issue of FTFs and FFs; also, the impact of the FTFs and FFs on Estonia’s as well as the EU’s border management is analysed. Major conclusions of the study include the suggestion to use smart gates for the biometric verification of all passengers within the Schengen area as well as the suggestion for the Baltic States to create and develop multi-agency framework for treatment of returnees and refugees from conflict zones.